Healthy Snack Education Using Role Playing Method to Improve Knowledge, Healthy Living Attitudes and Nutrients Primary School Students - Alvianti, Neily Widya; Dewi, Yulia Lanti Retno; Qadrijati, Isna (Nusantara Science and Technology Proceedings, 2024)
Nutritional problems are experienced by the population in Indonesia, including elementary school-age children. Data from the 2020 nutritional status assessment in East Kalimantan recorded 7.4 percent of underweight nutritional status experienced by children of that age. Elementary school children have the habit of consuming snacks without considering the nutritional content and certain substances that are dangerous to health. Several studies have found that snacks consumed by school children contain dangerous substances. Education on healthy snacks for elementary school-age children is important to increase knowledge of healthy snacks, healthy living attitudes, and nutritional content. Healthy snacks education can be done through the roleplaying method (RPM). This study aims to analyze the effect of healthy snacks education using RPM on knowledge of healthy snacks, healthy living attitudes, and nutrition in elementary school students. This research method is a quasi-experiment. This research used a pretest-posttest control group design. The research subjects of SD/MI Darussalam students were 60 people who were selected purposively. A total of 30 people were designated as the experimental group and 30 people as the control group. The research instruments were digital weight scales, microtoises, tests, questionnaires and food recall forms. Data analysis uses univariate and bivariate analysis. Normally distributed data was analyzed using the T-Test, and data that was not normally distributed was analyzed using the Mann-Whitney U Test. The research results showed that providing healthy snacks education using RPM had a significant effect on students' knowledge of healthy snacks (p < 0.05), students' healthy living attitudes (p < 0.05), and students' nutrition (p < 0.05). The implication of the research is that providing education on healthy snacks using RPM is important for students in every elementary school because this education has been proven to significantly increase students' knowledge about healthy snacks and can improve healthy living attitudes and students' nutrition (271 words).